Quantum groups and knot algebra by tom Dieck T.

By tom Dieck T.

Similar abstract books

Intégration: Chapitres 7 et 8

Intégration, Chapitres 7 et 8Les Éléments de mathématique de Nicolas BOURBAKI ont pour objet une présentation rigoureuse, systématique et sans prérequis des mathématiques depuis leurs fondements. Ce quantity du Livre d’Intégration, sixième Livre du traité, traite de l’intégration sur les groupes localement compacts et de ses functions.

Additional resources for Quantum groups and knot algebra

Example text

4) We use that s is an antihomomorphism of coalgebras, i. e. the relation µs = τ (s ⊗ s)µ. To begin with, Λ is an isomorphism of A ⊗ A0 ⊗ A0 -modules with actions ((a ⊗ b ⊗ c) · ϕ)(x ⊗ y) = aϕ(bx ⊗ cy) left ((a ⊗ b ⊗ c) · ψ)(x)(y) = a(ψ(bx)(cy)) right. The A-module structure on the left side uses (1 ⊗ µs)µ, on the right side ((1 ⊗ s)µ ⊗ 1)(1 ⊗ s)µ = (1 ⊗ τ )(1 ⊗ s ⊗ s)(µ ⊗ 1)µ. Coassociativity of µ and antihomomorphy of s yield the equality. (5) The definitions give T (a · (ϕ ⊗ ψ))(y ⊗ x) = ϕ(s(a1 )x)ψ(s(a2 )y).

32 1 Tensor categories T. 4) Theorem. The left dual f ∗ and the right dual f # coincide. Proof. The morphism f # is characterized by (f # 1) ◦ aV = (1f ) ◦ aV . The morphism f ∗ by a similar equality with the b-morphisms. If we apply (δ1) ◦ z and (1δ) ◦ z to this characterization of f ∗ , we obtain (f ∗ 1 ◦ aV = 1f ◦ aV . We conclude f # = f ∗ . 5) Theorem. The morphisms I bV ✲ VV∗ f 1✲ VV∗ cV ✲ I I aV ✲ V ∗V 1f ✲ V ∗V dV ✲ I coincide for each endomorphism f : V → V . Proof. We insert the definition of aV and cV and use the naturality of z and δ.

10) Example. Let A be cocommutative. Then the dualization H(M, N ) → H(N ∗ , M ∗ ), ϕ → ϕ∗ is A-linear. ♥ T. tom Dieck 4. 11) Example. Let A be cocommutative. Then the tautological map H(M1 , N1 ) ⊗ H(M2 , N2 ) → H(M1 ⊗ M2 , N1 ⊗ N2 ), ϕ⊗ψ →ϕ⊗ψ ♥ is A-linear. 4. The finite dual Let A be a Hopf algebra over a field K. We use finite dimensional A-modules to construct the finite dual of A. The algebra A acts on the left and right on the dual vector space A∗ by (a · f )(x) = f (xa) and (f · a)(x) = f (ax).